Effects of cultivation on the organic matter of grassland soils as determined by fractionation and radiocarbon dating - Martel, Y. A., author; Paul, Eldor A., author; Agricultural Institute of Canada, publisher (Colorado State University. Libraries, 1974)
The effects of cultivation on the net mineralization of carbon and nitrogen in a lacustrine Brown clay (Sceptre) and two Orthic Black soils on glacial till (Oxbow) were assessed with the aid of fractionation and radiocarbon dating techniques. Fractionation of the soil organic matter of comparative virgin and cultivated soils by acid hydrolysis and peptization in dilute NaOH showed that the distribution of carbon and nitrogen among fractions of these soils was similar. There was no measurable alteration in the mean residence time (MRT) of the soil during the first 15 to 20 yr of cultivation, during which time the Sceptre soil had lost 19% of its carbon and the Oxbow, 35%. However, the MRT increased from 250 yr before present (BP) to 710 years BP after 60 yr of cultivation of the Oxbow soil. The losses for nitrogen were 10% lower than for carbon in the Oxbow soil due to the recycling of nitrogen in the soil. The rate of loss of carbon from the Oxbow soil during the cultivation period was simulated by expressing it as the sum of two first order reactions using fractionation and carbon dating data as the variables.
Keywords: grassland soil; organic matter; cultivation; decomposition; nitrogen; carbon; kinetics